2018
DOI: 10.3897/zookeys.784.26521
|View full text |Cite
|
Sign up to set email alerts
|

A first phylogenetic analysis reveals a new arboreal tarantula genus from South America with description of a new species and two new species of Tapinauchenius Ausserer, 1871 (Araneae, Mygalomorphae, Theraphosidae)

Abstract: Based on molecular and morphological phylogenetic analyses a new genus of Theraphosidae is described, Pseudoclamorisgen. n.Tapinaucheniusgigas and Tapinaucheniuselenae are transferred to Pseudoclamoris and a new species of Pseudoclamoris from the Amazon Region is described: P.burgessisp. n. Two new species of Tapinauchenius from the Caribbean are described: T.rastisp. n. and T.polybotessp. n.Tapinaucheniussubcaeruleus is considered a nomen dubium. Psalmopoeinae subfamily is diagnosed based on molecular and mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 30 publications
3
11
0
Order By: Relevance
“…may represent an ancient biogeographic relic and the novel placement indicated by our new results certainly warrants further study. The placements of Aviculariinae, Psalmopoeinae and Schismatothelinae together as other relatively derived subfamilies is consistent with the multigene results of Lüddecke et al (2018), which also recovered a corresponding clade for these, inline with other results from single genetic fragments (Turner et al, 2018;Hüsser, 2018).…”
Section: A First Phylogenomic Overview Of Theraphosidaesupporting
confidence: 85%
See 4 more Smart Citations
“…may represent an ancient biogeographic relic and the novel placement indicated by our new results certainly warrants further study. The placements of Aviculariinae, Psalmopoeinae and Schismatothelinae together as other relatively derived subfamilies is consistent with the multigene results of Lüddecke et al (2018), which also recovered a corresponding clade for these, inline with other results from single genetic fragments (Turner et al, 2018;Hüsser, 2018).…”
Section: A First Phylogenomic Overview Of Theraphosidaesupporting
confidence: 85%
“…Guadanucci, 2014), although some were also placed in a separate subfamily, "Psalmopoeinae" by other authors (Samm and Schmidt, 2010). Recently, Lüddecke et al (2018) andTurner et al (2018) found molecular evidence for the validity of the subfamily, which shortly thereafter was supported by both morphological and molecular data in Hüsser (2018), Consistent with these studies, our phylogenomic analysis further supports the distinction between Aviculariinae and Psalmopoeinae (including Ephebopus), as evidenced by both the high bootstrap support, and by the fact that, once again, Schismatothelinae were found to be closer to Psalmopoeinae than Aviculariinae, which was placed basal to both of these other subfamilies.…”
Section: Implications For Subfamilial Validity In Theraphosidaementioning
confidence: 85%
See 3 more Smart Citations